2005
DOI: 10.1055/s-2005-872238
|View full text |Cite
|
Sign up to set email alerts
|

Open-Cage Fullerenes: Synthesis, Structure, and Molecular Encapsulation

Abstract: The carbon-carbon bond scission of the fullerene cage offers an open-cage fullerene derivative having an opening on the fullerene surface. This account summarizes our recent studies on the syntheses of open-cage C 60 derivatives as well as their properties of molecular encapsulation. The photochemical rearrangement of the cyclohexadiene derivative of C 60 gives bis(fulleroid), the precursor for the cage scission. The photooxygenative carbon-carbon bond cleavage of bis(fulleroid) affords an open-cage diketone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…Due to the unique spherical structure of the fullerene cage, functional groups on the rim of the orifice usually exhibit unusual reactivity differing from that of classical organic compounds. For example, the orifice‐expansion reactions reported by Iwamatsu and Yeh are very efficient in making open‐cage fullerenes with a very large orifice. But these reactions are observed only for open‐cage fullerenes not for normal organic compounds.…”
Section: Figuresupporting
confidence: 80%
“…Due to the unique spherical structure of the fullerene cage, functional groups on the rim of the orifice usually exhibit unusual reactivity differing from that of classical organic compounds. For example, the orifice‐expansion reactions reported by Iwamatsu and Yeh are very efficient in making open‐cage fullerenes with a very large orifice. But these reactions are observed only for open‐cage fullerenes not for normal organic compounds.…”
Section: Figuresupporting
confidence: 80%
“…[44] The reaction of amino-compounds with open-cage fullerene derivatives is an efficient method to form large holes capable of incorporating small molecules. [52] Iwamatsu and coworkers found that hydrazine or hydrazone or phenylenediamine reacted with the ketolactam 25 to form compounds 44 [53] and 45.…”
Section: Hole-enlargement Reactionsmentioning
confidence: 99%
“…It was prepared in four steps in a total of 33% (2a) or 38% (2b) yield from [60]fullerene. [26][27][28] Orifice expansion of a singlet oxygen oxidized precursor 1 with 1,2-phenylenediamine is the key step for the formation of 20-membered ring orifice in this compound. Structures of 2 were assigned by spectroscopic data.…”
Section: Open-cage Fullerenes From 12-phenylenediaminementioning
confidence: 99%